Tantangan Hate Speech di Universitas Islam Negeri Jakarta Pada Masa Permira 2023 - Azzahra, Lulu Fatimah; Kahfi, Ahmad Diomedes Al; A, M Dzarres Jiddan; khoirotunnisa, Pia (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research aims to analyze the challenges of hate speech during the 2023 Permira (student general election) at UIN Jakarta. The research method used is a case study with data collection techniques through observation, interviews, and document analysis. The research results show that hate speech appears in various forms, including expressions of hatred, insults, and provocations directed at individuals or groups based on ethnicity, religion, race, and certain groups. Hate speech is expressed through social media, online forums, and candidate debates. Hate speech has a negative impact on the democratic process at UIN Jakarta, namely creating tension and conflict and dividing students' sense of unity. Hate speech also disrupts the student election process, damages individual reputations, and endangers the safety and welfare of the targeted individuals.